Design and development of a bottle cap opening device - Kok, Yane Jun Yan (2018)
Bottle caps have always been a pain in opening them. It is especially so for the elderly or people with weaker grips. According to research, it is known that as people age, their grip strength decreases. This comes along with the natural disadvantage in opening bottle caps. Although there are many products out in the market, there is still a need for a design which can limit the use of human effort. Thus, the aim of this project is to design a bottle cap opener which can do so. The project starts with a conceptual phase whereby designs are rough and unpolished. By brainstorming various ideas using methods such as function analysis and morphological chart, ideas were streamlined using the weighted evaluation matrix, before coming to a final design. Next stage is to refine the design using SolidWorks and come out with dimensions and parts needed to bring the idea to life. The idea consists of an upper movable system, a rotation system and a gripping system. Theoretical calculations were done to see if the torque produced by the design was sufficient in reducing the forces needed Lastly, a prototype would be manufactured as to ensure the feasibility of the product in real world scenarios. Due to time constraints, the author could not finish the prototype. Recommendations and improvements will also be listed to help the next person who embarks on this project or design.